2014
DOI: 10.1517/17460441.2014.883377
|View full text |Cite
|
Sign up to set email alerts
|

The discovery and development of cyclooxygenase-2 inhibitors as potential anticancer therapies

Abstract: There have been a number of PTGS2 (COX-2) selective inhibitors suggested as potential anticancer therapies. In recent years, the development of nanotechnology has also had an impact on chemotherapy. Indeed, nanoparticles of cytotoxic drug carriers have demonstrated potential through their accumulation in cancer cells, and targeting these nanoparticles has been under evaluation. This area could be opened up for coxib development as they are potentially important targets in cancer cells. Further research using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 94 publications
0
56
0
Order By: Relevance
“…14,15,43,44 However, the application of Celecoxib over a prolonged period of time seems to be critical since it may cause cardiovascular side effects. 12 Moreover, the effect of Celecoxib alone induced different effects on pancreatic cancer cells. 12,45 In our experiments, we used different Cox inhibitors, which did not induce cell death or cell cycle arrest in PDAC cells in the used concentrations but inhibited the PGE2 release.…”
Section: E988460-8 Volume 4 Issue 3 Oncoimmunologymentioning
confidence: 99%
See 3 more Smart Citations
“…14,15,43,44 However, the application of Celecoxib over a prolonged period of time seems to be critical since it may cause cardiovascular side effects. 12 Moreover, the effect of Celecoxib alone induced different effects on pancreatic cancer cells. 12,45 In our experiments, we used different Cox inhibitors, which did not induce cell death or cell cycle arrest in PDAC cells in the used concentrations but inhibited the PGE2 release.…”
Section: E988460-8 Volume 4 Issue 3 Oncoimmunologymentioning
confidence: 99%
“…12 Moreover, the effect of Celecoxib alone induced different effects on pancreatic cancer cells. 12,45 In our experiments, we used different Cox inhibitors, which did not induce cell death or cell cycle arrest in PDAC cells in the used concentrations but inhibited the PGE2 release. Our data demonstrate that a combined immunotherapy with Cox-2 inhibitors together with the newly designed tribody [(Her2) 2 £Vg9] gives us a tool to efficiently induce the gd T cell-mediated lysis of Colo357 PDAC cells.…”
Section: E988460-8 Volume 4 Issue 3 Oncoimmunologymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, selective COX-2 inhibitors such as celecoxib have been included in clinical trials in non-small-cell lung cancer patients showing promising results [26][27][28]. Moreover, results from another clinical trial in adenoma cancer patients showed significant benefit effect in the celecoxib group of patients [29].…”
Section: Introductionmentioning
confidence: 99%